A social-ecological systems approach is necessary to achieve land degradation neutrality. Issue 89 (November 2018) - Okpara, Uche T.; Stringer, Lindsay C.; Akhtar-Schuster, Mariam; Metternicht, Graciela I.; Dallimer, Martin; Requier-Desjardins, Mélanie
Highlights: LDN is not a social norm and its framing is yet to recognise how people structure their thinking about neutrality issues. SES-based LDN approach reveals what it means to consider humans as part of nature in the pursuit of LDN. SES science and practice can inspire progress towards identifying appropriate LDN baselines for tracking change. Abstract: Viewing humans as drivers of change operating outside the natural environment is unhelpful for defining interventions that effectively manage change and complexity. Indeed, there is now broad agreement that environmental governance needs to consider integrated social-ecological systems (SES) in order to tackle the world's grand challenges of land degradation. This requires a more differentiated, innovative approach that considers how changes in SES shape the functioning of land systems as a whole, and the synergies and trade-off these changes may produce. In this study, we identify and discuss some of the ways SES science and practice can inspire progress towards land degradation neutrality (LDN) outcomes in an integrated manner, through synthesis of literature and relevant documents related to the United Nations Convention to Combat Desertification (UNCCD). We do these by considering: (i) how LDN has been approached to date and the challenges likely to undermine progress towards achieving it; and (ii) an SES-based LDN approach relevant to the neutrality agenda, in particular, by describing how LDN might be thought of differently through an SES lens. We argue that an SES approach focusing on: (i) "people as part of nature", not "people and nature"; and (ii) the frame of reference against which neutrality can be assessed across temporal and spatial dimensions, is necessary to both inform policy and guide actions of the different groups involved in avoiding and combating land degradation. Such an (integrated) approach adds a dimension (to achieving neutrality goals) not previously explored in sustainable land management and LDN research. Important next steps in operationalising the SES-based LDN approach involve empirical and field case studies, requiring interdisciplinary, mixed method techniques.